2018
DOI: 10.1002/ejoc.201800063
|View full text |Cite
|
Sign up to set email alerts
|

Deacylative Reactions: Synthetic Applications

Abstract: Herein we introduce the recent developments of a new strategy based on deacylative alkylation (DaA) reactions for the generation of quaternary stereocenters based on the in situ preparation and functionalization of enolates under very mild reaction conditions. Palladium‐catalyzed deacylative allylation and benzylation reactions of carbon nucleophiles are performed with the corresponding alcohols. This methodology has been applied to the synthesis of the calcium ion channel blocker verapamil, the antiviral (+)‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…[1,2,6] Some successi nt his area has been achieved with the development of enantioselective electrophilic fluorination, [7] whereas the alternative approaches still represent af ormidable challenge. [8] Owingt ot he multifaceted biological properties of oxindole derivatives, an umber of research groupsh ave reported catalytic enantioselective elaboration of 3-fluorooxindole-derived enolates 1 (Scheme 1) by aldol or Mannich reactions, [9] conjugate additions [10] and allylic alkylations [11] offering efficient access to av ariety of structurally novel compounds of high biological importance.C onsistent with our long-standing interest in catalytic asymmetric synthesis of fluorine-containing compounds, [12] we wanted to develop the Colby pro-enolates of type 2 [8b, [13][14][15][16] as synthetic alternatives to the conventional fluoro-enolates. [17] In particular, we reported the design of 3fluorooxindole derived pro-enolates 2, [18] and their unusual reactivity with imines [18,19] and dialkyl azodicarboxylates.…”
mentioning
confidence: 99%
“…[1,2,6] Some successi nt his area has been achieved with the development of enantioselective electrophilic fluorination, [7] whereas the alternative approaches still represent af ormidable challenge. [8] Owingt ot he multifaceted biological properties of oxindole derivatives, an umber of research groupsh ave reported catalytic enantioselective elaboration of 3-fluorooxindole-derived enolates 1 (Scheme 1) by aldol or Mannich reactions, [9] conjugate additions [10] and allylic alkylations [11] offering efficient access to av ariety of structurally novel compounds of high biological importance.C onsistent with our long-standing interest in catalytic asymmetric synthesis of fluorine-containing compounds, [12] we wanted to develop the Colby pro-enolates of type 2 [8b, [13][14][15][16] as synthetic alternatives to the conventional fluoro-enolates. [17] In particular, we reported the design of 3fluorooxindole derived pro-enolates 2, [18] and their unusual reactivity with imines [18,19] and dialkyl azodicarboxylates.…”
mentioning
confidence: 99%
“…Initially, the keto‐esters 7 were treated with K 2 CO 3 (1 equiv) in refluxing acetone. Under these conditions, the presence of the hydroxy group on the concave face of 7 facilitated a retro‐Claisen condensation, affording lactones 11 in very good yields and with excellent optical purity ( 11 a , 11 b , 11 f , 11 g , 89–93 % yield, >99 % de, 91–97 % ee ; Scheme ). Moreover, when 7 a was treated with K 2 CO 3 followed by EtONa in refluxing EtOH, the bridged bicyclic compound 12 a (80 % yield, >99 % de; Scheme ) was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…With the aim of illustrating the versatility of the ester handle,t he next part of the investigation looked at the reactions of compounds of type 7 with bases.I nitially,t he keto-esters 7 were treated with K 2 CO 3 (1 equiv) in refluxing acetone.Under these conditions,the presence of the hydroxy group on the concave face of 7 facilitated ar etro-Claisen condensation, [15] affording lactones 11 in very good yields and with excellent optical purity (11 a,11 b,11 f,11 g,> 99 %de,(91)(92)(93)(94)(95)(96)(97)Scheme 6). Moreover,when 7a was treated with K 2 CO 3 followed by EtONa in refluxing EtOH, the bridged bicyclicc ompound 12 a (80 %y ield, > 99 %d e; Scheme 6) was obtained.…”
Section: Angewandte Chemiementioning
confidence: 99%